2015
DOI: 10.1007/s00586-015-3971-5
|View full text |Cite
|
Sign up to set email alerts
|

Does patient perception of shoulder balance correlate with clinical balance?

Abstract: We have not found a significant correlation between clinical/radiological ShB and perceived ShB in non-operated IS patients. It seems that ShB is not a key factor in patient trunk deformity perception. In addition, patient expectations regarding improvement with treatment are not directly related to actual clinical imbalance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…The difference in 10 mm in RSH was chosen as it has been described as the minimal threshold for clinically significant difference in shoulder height. 3,19 This analysis confirmed that the present study is adequately powered.…”
Section: Discussionsupporting
confidence: 84%
“…The difference in 10 mm in RSH was chosen as it has been described as the minimal threshold for clinically significant difference in shoulder height. 3,19 This analysis confirmed that the present study is adequately powered.…”
Section: Discussionsupporting
confidence: 84%
“…Whilst considered a key factor in the perception of trunk deformity in scoliotic patients [ 25 , 27 ], it has recently been suggested that patients’ perceptions of their shoulder deformity do not correspond with clinical measures of shoulder balance. Using clinical photography, Matamalas et al [ 33 ] demonstrated no correlation between clinical measures of shoulder balance and patients’ perceptions of their deformity in non-operated scoliotic patients, calling into question the value of shoulder balance in the overall assessment of trunk deformity. Interestingly in a normal study population, Akel et al [ 34 ] found that 28% had a shoulder imbalance greater than 10 mm.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Surgeons' primary aim had always been correcting the coronal curvature. However, PSI became a concern as patients' perspective on their postoperative appearances including shoulder balance was found to be imperative in determining the cosmetic outcomes of the surgery [8][9][10][11][12][13][14][15][16][17][18][19][20][21]22 The focus of surgical concern was then shifted to achieve a balanced postoperative shoulder instead. Various methods were introduced to circumvent PSI such as upper thoracic spine leveling, upper instrumented vertebra (UIV) level selection, UIV tilt angle, fusion level selection, preoperative shoulder balance, proximal thoracic (PT) correction rate and its extent of correction of main thoracic (MT) curve.…”
Section: Introductionmentioning
confidence: 99%